LACTATE-ALBUMIN DIFFERENCE IN MEDICAL AND SURGICAL INTENSIVE CARE UNITS - (:unkn) unknown (NOBEL ILAC, 2021)
Objective: Sequential Organ Failure Assessment (SOFA) score, lactate, and lactate-albumin difference values obtained at admission to surgical and medical intensive care units are evaluated for cutoff values and predictive significance on mortality. Material and Method: Data between 2001 and 2012 were extracted from MIMIC-III database. Adult patients admitted to the medical and surgical intensive care unit for the first time were evaluated. The significances of the SOFA score, maximum lactate, and lactate-albumin difference values in predicting mortality were analyzed, and cutoff values are determined. Results: Non-survivors had higher lactate, higher lactate - albumin difference, and lower albumin values than survivors (p<0.001, for all). In surgical intensive care units, lactate, lactate - albumin difference, length of hospital and intensive care unit stays were higher, but 30- and 90-day mortalities were lower than medical intensive care units. SOFA scores were similar (p=0.30). The area under the receiver operating characteristic curve (AUC) of SOFA score (AUC = 0.776, 95% CI: 0.735-0.817) and the cutoff value were greater in the surgical intensive care unit than the medical one (AUC=0.762, 95% CI: 0.745-0.780). The AUC of overall lactate - albumin difference (AUC=0.713, 95% CI: 0.695-0.731) was larger than overall maximum lactate (AUC=0.680, 95% CI: 0.662-0.699) on the first day. Both the maximum lactate and lactate - albumin difference cutoff values were higher in the surgical intensive care unit. Conclusion: Lactate - albumin difference's predictor value of mortality was superior to initial minimum albumin and maximum lactate values. Different cutoff values of the SOFA score, lactate - albumin difference, and maximum lactate should be used in medical and surgical intensive care units.
Keywords: Lactate; albumin; lactate - albumin difference; intensive care unit; ORGAN FAILURE; MORTALITY; OUTCOMES; ADULTS; SCORE